ANALISIS KASUS TINDAK PIDANA PEMBUNUHAN MOTIF, ALAT BUKTI, PENERAPAN PASAL DAN VONIS - Karmila; Rahma Daniati; Winarti; Wulan Sari; Komang Juntika; Henny Anastasya Meilani; Dina Selvia Ningsih; Ian Sagita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the case of premeditated murder committed by Ferdy Sambo against Brigadier Nofriansyah Yosua Hutabarat (Brigadier J). The purpose of this research is to understand the motive, evidence, application of legal articles, and the verdict imposed from the perspective of Indonesian criminal law. The research method used is normative juridical, employing a statutory approach based on Article 340 of the Indonesian Criminal Code (KUHP) concerning premeditated murder, as well as Law No. 19 of 2016 on Electronic Information and Transactions. The results of the study indicate that this case represents a deliberately planned act of murder involving several parties, including elements of obstruction of justice in an attempt to cover up the crime. Evidence such as autopsy results, witness testimonies, and the confession of Bharada E strengthen the conclusion that the murder was premeditated. The South Jakarta District Court initially sentenced Ferdy Sambo to death, a decision upheld at the appellate level. However, at the cassation stage, the Supreme Court commuted the sentence to life imprisonment. This case reflects a crisis of integrity among law enforcement officials and serves as a representation of the application of justice and legal certainty within Indonesia’s criminal justice system.